L'ONU au Cambodge. Les leçons de I'APRONUC (Note) - Jennar, Raoul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1995)
The UN operation in Cambodia was a major venture provided with extensive resources and entrusted to implement a highly ambitious program contained in the Paris Accords signed on October23, 1991. Today, official rhetoric speaks of a "model" when referring to what a more modest view would treat as an experience - one from which it is indispensable to draw all the lessons. The UN proved unable to carry out much of its mission. It jailed to disarm the rival troops. It jailed to neutralize the Communist party's omnipresent influence over existing administrative structures. It failed to repair or rebuild a minimum of infrastructure in such basic areas as health, education, and communications. It failed to reintegrate into society the 372,000 refugees who had come back from camps in Thailand. It failed to preserve the country's unity and territorial integrity. Yet it did score some successes. It laid the ground work for a pluralistic society. It repatriated the refugees. It organized elections that were free and fair enough to allow new, thoroughly legitimate institutions to come into being. A cautious assessment of this operation leads to a reflection on the conditions for success or failure of such a venture. Lessons are to be learned from each step : starting from the diplomatic moves behind the decision to carry out the operation and the mandate defining its scope ; and ending with the political, economic, and social repercussions due to thousands of soldiers and foreign civilian administrators passing through the country. Each phase of the flow of operations must also be questioned, from recruitment of personnel to assessment of the results obtained.